Financial frictions: Micro vs. macro volatility - Renato Faccini; Seungcheol Lee; Ralph Luetticke; Morten O. Ravn; Tobias Renkin (Danmarks Nationalbank, 2024)
Consumer credit spreads significantly impact consumption and asset dynamics, affecting indebted households' spending behavior and the income sensitivity of consumption. Analyzing Danish data, we find that elevated credit spreads reduce consumption of indebted households. Our results suggest that the marginal propensity to consume (MPC) is countercyclical, with credit spreads playing a crucial role. We develop a HANK model, incorporating bank financing for both firms and households. Agency frictions generate a countercyclical credit spread, which induces heterogeneous incidence of aggregate shocks consistent with the data. Banking regulation, while stabilizing at the aggregate level, may induce volatility at the household level.
Keywords: C11; D12; D31; E32; E52; G51; 330; Household consumption; consumer credit spreads; business cycles; financial frictions; incomplete markets; macroprudential regulation; monetary policy